The scenario of Violence against Women in Bangladesh: A Trend Analysis - Monir Ahmed; Huda, Kazi Nazmul; Shakina Sultana Pomi (Technium Social Sciences Journal, 2022)
The prime objective of this study is to portraythe current trend of violence against Bangladeshi women. Using the survey report on violence against women (VWA) conducted by Bangladesh Bureau of Statistics, this paper has examined the patterns and trends of gender violence in Bangladesh.This study revealed thatsexual violence against women is a great concern for Bangladesh as the rate is not decreasing notably. However, the trend of emotional violence is declining notably. The study recommended some specific preventive interventionsincluding counseling and emergency response center to minimize the VAW in Bangladesh. The results of this study will facilitate the researchers and policymakers to predict the future trend of VAW and formulate the necessary plan of action to prevent this social disorder.